Analytical Prediction of the Distortional Buckling Loads for Cold-Formed Channel Beams with Edge-Stiffened Rectangular Web Openings - Can Liu; Liping Duan (Buildings, 2022)
Recently, there has been an increasing number of studies on the distortional buckling analyses of cold-formed steel (CFS) channels with web edge-stiffened holes. However, the literature about the analytical solutions is scarce, and the current design rules, e.g., the American Iron and Steel Institute (AISI 2016) and the Australian/New Zealand standards (AS/NZ 4600: 2018), provide little design advice for CFS channels with edge-stiffened holes. This paper presents an analytical method for estimating the bearing capacity for the distortional buckling of CFS channel beams with edge-stiffened rectangular web holes. To validate the proposed method, comprehensive finite element (FE) analyses were performed. The proposed design equations accurately forecast the distortional buckling moment capacities of the CFS channels with edge-stiffened holes. Specifically, the average error of the critical moment predictions for the distortional buckling of perforated CFS channel beams obtained by the proposed analytical method and the finite element method (FEM) is only 6.59%, where the maximum error reaches 17.76%. Moreover, a parameter study on the effect of the edge-stiffener length on the bearing capacity was carried out as well, and the results show that the edge stiffener indeed significantly enhanced the critical moment when it is below a threshold length, but the enhancement becomes unobvious once surpassing the threshold length.